Bone-Anchored Hearing Implants: Surgical and Audiological Comparison of Different Surgical Techniques - Topcu, Merve Torun; Mutlu, Basak; Celik, Serdal; Celikgun, Bahtiyar; Mutlu, Ahmet; Kalcioglu, M. Tayyar (International Archives of Otorhinolaryngology, 2022)
Introduction The bone-anchored hearing implant system (BAHS) is an effective amplification system that transmits the sounds received by an external operating system to the inner ear by bypassing the middle ear placed in the temporal bone.Objective This study compares the results of patients who underwent bone-anchored hearing implant system (BAHS) surgery using two different surgical methods in terms of preoperative and postoperative complications, surgical time, audiological findings, and patient satisfaction.Methods The results of 22 patients who underwent BAHS were evaluated retrospectively from video records and audiological results, The Turkish Version of the Glasgow Benefit Inventory (GBI) questionnaire were evaluated. Two different surgical approaches were used for implantation: the linear incision technique (n = 9) and the punch technique (n = 13).Results Mean surgical durations were 9.67 ± 2.85 and 47.65 ± 6.13 minutes for Groups A and B, respectively, and these were significantly different (p < 0.001). There were no significant differences between the groups' speech recognition scores for a signal-to-noise ratio (SNR) of +5 (p = 0.173), SNR of 0 (p = 0.315), or SNR of -5 (p = 0.360) and results of the GBI scores.Conclusion The punch technique has a significant advantage due to a shorter surgery duration without increased surgical complications. Additionally, the punch technique showed no significant difference in hearing performance or satisfaction compared with linear incision.
Keywords: bone-anchored implants; quality of life; hearing tests; punch technique; linear incision technique